Respecting dignity: A fundamental element of the ethical being's existence - Ljupcho Chakar*; Aleksandar Stankov; Goran Pavlovski; Natasha Bitoljanu; Viktorija Belakaposka Srpanova; Ana Ivcheva; Rosica Siamkouri; Zlatko Jakovski (Makedonsko Farmacevtski Bilten)
Human dignity is a pivotal concept in contemporary ethical, political, and legal discourse. However, divergent and sometimes conflicting interpretations of human dignity contribute to confusion across various discussions. Given that all human beings possess inherent moral potential, each individual is endowed with universal dignity. The extent to which people develop their moral potential varies. Discussing an individual’s dignity, as in other medical specialties, cannot be separated from forensic medicine as a distinct medical discipline. In conclusion, the authors assert that establishing medical facts, or the truth ascertained through expert examination, serves justice by ensuring dignified treatment of the deceased, their family, and relatives.